Estabelecimento e multiplicação in vitro de oliveira para início da micropropagação. - Donini, Lorena Pastorini (2009)
The olive (Olea europaea L.) belongs to the Oleacea falmily, which include until 30 genera and 600 species distributed in tropical and temperate regions. The cutting is a widely used method, however the in vitro culture by micropropagation is a viable method of propagation providing the uniformity to the orchards, besides to enable the production of plants with health and accelerate the methods of conventional propagation. Thus, this work aimed to evaluate in vitro establishment and multiplication of olive through different treatments of culture medium. The article 1 aimed the in vitro established of different olive cultivars under different types of light and to evaluate combinations of zeatin and gibberellic acid of the in vitro establishment. The article 2 aimed to determine both the suitable culture medium and zeatin concentration for in vitro establishment of olive tree cv. Arbequina. The objective of article 3 was find alternatives to replace the use of zeatin or decrease this concentration in the culture medium to evaluate different cytokinins and concentrations of in vitro establishment and multiplication of olive tree cv. Arbequina. The article 4 aimed to evaluate two sugar types and concentrations on in vitro multiplication of olive cultivar Arbequina. The article 5 evaluated different types of closing and silver nitrate of in vitro multiplication of olive tree cultivar Arbequina. It was verified that: (1) the cultivars Koroneiki e Picual presented higher rate of in vitro establishment when cultivated under white light; the zeatin and AG3 combination is not efficient for in vitro establishment of olive tree; (2) the WPM and MO medium culture provide better results on in vitro establishment of olive cultivar Arbequina; (3) the use of 2 mg L-1 BAP is efficient for establishment and the use of 2 mg L-1 zeatin is efficient on in vitro multiplication of cultivar Arbequina; (4) Sucrose provides better results and the use of 15 g L-1 of sucrose is efficient as sugar source on in vitro multiplication of cultivar Arbequina; (5) the use of aluminum as sealing and the addition of 10 mg L-1 silver nitrate in the MO culture medium presents better results on in vitro multiplication of olive tree cultivar Arbequina.